Mechanical properties and durability of concrete with recycled air-cooled blast furnace slag aggregates - Osama A. Mohamed; Osama Ghanam; Ahmed Hamdan; Mohammad Zuaiter; Tae-Yeon Kim (Scientific Reports)
Abstract This study evaluated the properties of concrete in which natural coarse aggregates were replaced with 30%, 50%, or 100% air-cooled blast furnace slag (ACBFS) aggregates. At all aggregates replacement levels, concrete porosity remained below 9.55%, indicating good quality concrete. The high friction between ACBFS aggregates and mortar when the w/b ratio was 0.4, was mitigated when the ratio was increased to 0.45, likely due to pore structure refinement at the interfacial transition zone (ITZ). When the ACBFS content exceeded 50%, chloride ion penetrability was rated as high, potentially limiting its use in durability-sensitive applications. However, increasing the ACBFS replacement percentage consistently enhanced compressive strength, likely due to the reaction between ACBFS and portlandite, forming additional C–S–H and resulting in a denser cementitious matrix. After 56 days, concrete with 100% ACBFS achieved 25.76% higher strength than the control mix with natural aggregates. ACBFS aggregates may have facilitated internal curing through moisture desorption, refining the pore structure within the matrix and interfacial transition zone (ITZ), as confirmed by SEM images. This study presents critical findings that support the use of recycled ACBFS in concrete for structural engineering applications, as a partial or complete replacement for natural coarse aggregates, thereby contributing to the conservation of natural resources.